2022
DOI: 10.1186/s12943-021-01481-w
|View full text |Cite
|
Sign up to set email alerts
|

CircRTN4 promotes pancreatic cancer progression through a novel CircRNA-miRNA-lncRNA pathway and stabilizing epithelial-mesenchymal transition protein

Abstract: Background Circular RNAs (circRNAs) play important roles in many biological processes. However, the detailed mechanism underlying the critical roles of circRNAs in cancer remains largely unexplored. We aim to explore the molecular mechanisms of circRTN4 with critical roles in pancreatic ductal adenocarcinoma (PDAC). Methods CircRTN4 expression level was examined in PDAC primary tumors. The oncogenic roles of circRTN4 in PDAC tumor growth and metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 63 publications
0
31
0
Order By: Relevance
“…Their results also suggested that circRTN4 may function as a sponge of miR-497-5p, which can also bind with lnc-HOTTIP. Thus circRTN4 can also contribute to the EMT via the miR-497-5p/ HOTTIP/HOXA13 pathway in PDAC (147,150).…”
Section: More Roles Of Circrna In Emtmentioning
confidence: 99%
“…Their results also suggested that circRTN4 may function as a sponge of miR-497-5p, which can also bind with lnc-HOTTIP. Thus circRTN4 can also contribute to the EMT via the miR-497-5p/ HOTTIP/HOXA13 pathway in PDAC (147,150).…”
Section: More Roles Of Circrna In Emtmentioning
confidence: 99%
“…Ultimately, it slowed the proliferation and metastasis of glioma cells and alleviated the cellular EMT process [134]. Interestingly, circular RNA (circRTN4) interacted with miR-497-5P to regulate the downstream RAB11FIP1 protein to block the ubiquitination, which inhibited Snail1/2, Twist, ZEB1, and N-cadherin to promote the metastasis of pancreatic ductal carcinoma cells [135]. miR-139-5p regulates the transcription factor Twist and the mesenchymal marker proteins N-cadherin and vimentin by targeting the sex-determining region Y-box protein 5 (SOX5) to achieve EMT inhibition [136].…”
Section: Mirnas Regulate Emt In Other Cancersmentioning
confidence: 99%
“…Pancreatic ductal adenocarcinoma (PDAC) has been the seventh leading cause of cancer death worldwide [92]. The researchers found that circ-0001666 acts as a sponge of miR-1251, the circRNA-associated ceRNA network further up-regulates SOX4 [93], and circRTN4 regulates the expression of Slug, Snai1, Twist, Zeb1, and N-cadherin in the EMT pathway by interacting with tumor suppressor miR-497-5p [94]. Circ-000510 acts as a sponge of miR-20a-3p and indirectly regulates the expression of COL11A1 [95]; circ-0092314 can promote the proliferation, migration, and invasion of pancreatic cancer cells by binding to miR-671 and alleviating the inhibition of its downstream target S100P [96]; circNEIL3 regulates the expression of ADAR1 by acting as a sponge of miR-432-5p, so as to induce RNA editing of GLI1, and ultimately affect the cell cycle progress and promote EMT [97].…”
Section: Circrna-associated Cerna Network In Pancreatic Cancermentioning
confidence: 99%